2017
DOI: 10.3389/fphys.2017.00407
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Excessive Exercise Attenuates the Anti-Inflammatory Effects of Exercise in Older Men

Abstract: Introduction/Purpose: A number of studies have investigated the effect of training with a moderate exercise dose (3–6 h/weekly) on the inflammatory profile in blood, and the data are inconsistent. Cross-sectional studies indicate a positive effect of physical activity level on inflammation levels and risk of metabolic disease. However, it is not clear whether this may be dose dependent and if very prolonged repeated exercise therefore may be beneficial for low-grade inflammation. Based on this we studied how e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Moreover, peritoneal macrophage functionality was altered, as observed with a higher production of IL-6 and IFN-γ, but lower secretion of IL-12, TNF-α and MCP-1. Higher IL-6 production is in line with increased plasma IL-6 concentrations reported in exercise 42,43 . Even though IL-6 has pleiotropic actions 44 , macrophages are the main cell source of this cytokine, which increased during and after exercise due to muscle damage 45 .…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, peritoneal macrophage functionality was altered, as observed with a higher production of IL-6 and IFN-γ, but lower secretion of IL-12, TNF-α and MCP-1. Higher IL-6 production is in line with increased plasma IL-6 concentrations reported in exercise 42,43 . Even though IL-6 has pleiotropic actions 44 , macrophages are the main cell source of this cytokine, which increased during and after exercise due to muscle damage 45 .…”
Section: Discussionsupporting
confidence: 76%
“…The increased levels of stress hormones may affect the activation and mobilization of immune cells [26, 27]. Sahl et al showed that among elderly adults, excessive physical activity increased plasma IL-6 concentrations and low-grade inflammation [28]. However, some studies found that physical activity reduced inflammation [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…13,19,20 The duration varied between 6 and 48 hours, some with 10 hours of daily exercise. 14,21,22 The present study is different in that we evaluated the concentration of IL-6 at the end of each of four days of long-term exercise. It is worth mentioning that the increase in IL-6 concentration depends on the intensity and duration of the exercise, so only 50% of the variation in plasma IL-6 concentration is due to the duration of the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The only other study conducted to date in this regard evaluated 14 days of cycling and the assays were performed only at the beginning and after the end of the 14-day course. 22 In addition, IL-6 was dosed in isolation as its elevation due to tissue damage stimulates an acute inflammatory response, which, alone or potentiating the effects of other cytokines, 5,15 induces the secretion of other markers (PCR, serum amyloid A, fibrinogen, and α1-antichymotrypsin) related to the inflammatory response. 16 IL-6 is a cytokine secreted by skeletal muscle during exercise, 11,27,32 and has been correlated with several biomarkers.…”
Section: Discussionmentioning
confidence: 99%